Reviving Roman religion: sacred trees in the Roman world - Hunt, Ailsa (Cambridge classical studies, 2016)
Rooting in: why give time to sacred trees? -- A brief history of tree-thinking: the enduring power of animism -- How arboreal matter matters: rethinking sacrality through trees -- Arboriculture and arboreal deaths: rethinking sacrality again -- Confronting arboreal agency: reading the divine in arboreal behaviour -- Imagining the gods: how trees flesh out the identity of the divine -- Branching out: what sacred trees mean for Roman religion